Minimally Invasive Acute Care Surgery (Springer International Publishing, 2018)
This text is designed to present a comprehensive, up to date and safe approach to managing emergency general surgery patients with a minimally invasive approach. This book bridges the gap between the minimally invasive surgery (MIS) expert who may not routinely be involved in the care of the acute care surgery patient and the ACS expert surgeon who may not have a routine MIS elective practice. The first section reviews the physiology of the acute care surgery patient and the physiologic impact of MIS techniques including pnemoperitoneum in critically ill patients. This review is crucial to assure that the surgeon has a clear understanding of when a MIS approach is safe and when it can be potentially dangerous to the patient. The illustrations are presented in an atlas-style format to describe the surgical procedures. The authors of the various sections are minimally invasive and acute care surgeons from prominent academic centers. The format represents a narrative review with appropriate illustrations and links to online videos.